2016
DOI: 10.1002/chem.201604455
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Charge‐Delocalized Two‐Dimensional Porphyrin System with Two Different Class III States

Abstract: Understanding of charge-delocalization over two-dimensional (2D) frameworks is a further step in the path towards the development of molecular nanodevices and nanomaterials. Here, we report a porphyrin-nickel complex with four peripheral redox-active ruthenium pendants (1). A cyclic voltammogram of compound 1 displays reversible five-electron, four redox waves with large potential separations, suggesting that one-electron- (1 ) and two-electron-oxidized species (1 ) are thermodynamically stable with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…37 Thus, using zinc(II) tetraphenylporphyrin (ZnTPP) as a central (prototypical) core, we have recently shown that tetra-Ru(II) derivatives, such as 4-X (Chart 2), [38][39] possess remarkable nonlinear absorptions around 550 nm and also in the near-IR range, relative to related unsubstituted porphyrins. In a continuation of these investigations, and inspired by the synthesis of related metal alkynyl-containing dendrimers 40 or porphyrins, 41 we have now undertaken the synthesis of the new compounds 5 n (n = 1, 2) which contain four Ru(κ 2 -dppe) 2 -based dendrons at the meso positions.…”
Section: -X (X = H No 2)mentioning
confidence: 99%
“…37 Thus, using zinc(II) tetraphenylporphyrin (ZnTPP) as a central (prototypical) core, we have recently shown that tetra-Ru(II) derivatives, such as 4-X (Chart 2), [38][39] possess remarkable nonlinear absorptions around 550 nm and also in the near-IR range, relative to related unsubstituted porphyrins. In a continuation of these investigations, and inspired by the synthesis of related metal alkynyl-containing dendrimers 40 or porphyrins, 41 we have now undertaken the synthesis of the new compounds 5 n (n = 1, 2) which contain four Ru(κ 2 -dppe) 2 -based dendrons at the meso positions.…”
Section: -X (X = H No 2)mentioning
confidence: 99%
“…[2d,i, 8] These results indicate that the odd electron of 1 3+ may be delocalized and the central ruthenium shows some Ru III character.M oreover,t he IVCT energy is solvent independent ( Figure S9). This is also the expected behavior for ac lass III MV compound, [8,15] suggesting the IVCT band arises from the electron resonance in the system rather than IVCT.The IVCT band of 2 3+ appears around l max = 8870 cm À1 (Table S7), and represents the ET processes between the terminal Ru II and the central Ru III .T his band is also cutoff and solvent independent ( Figure S10), indicating that 2 3+ may be ac lass II-III or class III MV compound. Ther eference compound 3 3+ shows similar LMCT and IVCT absorptions, but the metal-to-ligand charge-transfer (MLCT) band of terminal Ru still remains ( Figure S11).…”
mentioning
confidence: 79%
“…[8,14] The similar bands can also be observed in 2 3+ (17 168 cm À1 , 14 427 cm À1 )b ut are blue-shifted, which results from the oxidation of the central Ru II into Ru III .The IVCT band of 1 3+ appears around l max = 5045 cm À1 (Table S7) and is narrow and asymmetrical. This is also the expected behavior for ac lass III MV compound, [8,15] suggesting the IVCT band arises from the electron resonance in the system rather than IVCT.The IVCT band of 2 3+ appears around l max = 8870 cm À1 (Table S7), and represents the ET processes between the terminal Ru II and the central Ru III .T his band is also cutoff and solvent independent ( Figure S10), indicating that 2 3+ may be ac lass II-III or class III MV compound. [2d,i, 8] These results indicate that the odd electron of 1 3+ may be delocalized and the central ruthenium shows some Ru III character.M oreover,t he IVCT energy is solvent independent ( Figure S9).…”
Section: Electrontransfer(et)isafundamentalprocessinchemistrymentioning
confidence: 92%